OXYGEN ISOTOPE EXCHANGE BETWEEN DISSOLVED PHOSPHATE AND WATER AT TEMPERATURES =<135°C: INORGANIC VERSUS BIOLOGICAL FRACTIONATIONS - APPLICATION TO PALEOTEMPERATURE DETERMINATION - Lecuyer C.; Grandjean P.; Sheppard S.M.F. (My University, 1999)
Oxygen isotope fractionations have been measured experimentally between dissolved orthophosphate ions H2PO4- and water from 50°C to 135°C. The derived equilibrium fractionation equation reveals that biogenic apatites are systematically 18O-depleted (8%% at 20°C) compared with inorganic dissolved phosphate. The activation energy is relatively high at 134 kJmol-1 and the kinetics of the homogeneous inorganic exchange reaction are very slow (k = 10-13 to 10-11 s-1) when extrapolated to surface temperatures. In seawater, the oxygen isotope composition of dissolved phosphate is not in equilibrium with water; its composition should directly reflect source contributions or biological recycling. Any deviation from the composition of the inorganic sources may be attributed to biological recycling of this nutrient. The original isotopic compositions of fossils may be modified in less than 105 years at a temperature of 20°C through mechanisms of dissolution and precipitation in the presence of crustal aqueous fluids. The differences in oxygen isotope fractionations between biogenic or inorganic phosphate and water are applied to re-evaluate the significance of δ18O values of Phanerozoic and Precambrian phosphate deposits.
Keywords: Precambrian; Precambrian; Докембрий